Estimation metrics in software projects (2018)
A software product that implements a hybrid metric was developed. It articulates relevant characteristics of three estimation metrics in Communication and Information Technology (CIT) development projects: (i) history points, (ii) use case points, (iii) function points; as a planning strategy to control problems in software projects that tend to last longer than expected and generate higher costs. The Software product provides tools for making estimates based on expert judgments, planning poker and analogies with other projects that apply to agile projects. A descriptive statistical method was used in the first phase and an analytical method in the second phase. The analysis process is accomplished through the development of a Web application, used in the planning process of software projects in the Systems Engineering program of the Francisco de Paula Santander University. The article describes the characteristics implemented in each metric and its articulation process for the development of estimates. EstimaSoft is obtained as a result, as a support tool in the estimation of projects, in the identification of development trends, through the documentation of lessons learned.